2012
DOI: 10.1257/aer.102.6.2639
|View full text |Cite
|
Sign up to set email alerts
|

Sinking, Swimming, or Learning to Swim in Medicare Part D

Abstract: Under Medicare Part D, senior citizens choose prescription drug insurance offered by numerous private insurers. We examine nonpoor enrollees' actions in 2006 and 2007 using panel data. Our sample reduced overspending by $298 on average, with gains by 81 percent of them. The greatest improvements were by those who overspent most in 2006 and by those who switched plans. Decisions to switch depended on individuals' overspending in 2006 and on individual-specific effects of changes in their current plans. The olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
116
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(125 citation statements)
references
References 34 publications
9
116
0
Order By: Relevance
“…Above-minimum spending fell sharply from 2006-2007, similar to the results in Ketcham et al (2012). Under the assumption of perfectly inelastic demand, above-minimum spending fell by $173 (33 percent).…”
Section: Trends In Spending Switching and Savings From Switchingsupporting
confidence: 71%
See 2 more Smart Citations
“…Above-minimum spending fell sharply from 2006-2007, similar to the results in Ketcham et al (2012). Under the assumption of perfectly inelastic demand, above-minimum spending fell by $173 (33 percent).…”
Section: Trends In Spending Switching and Savings From Switchingsupporting
confidence: 71%
“…18 This high level of accuracy of the cost calculator comes from our ability to incorporate information and institutional knowledge held within CMS that were only partially incorporated into previous cost calculators ( Abaluck and Gruber 2011;Ketcham et al 2012). For example, this includes our ability to generate accurate underlying plan-specific prices, where the cost calculator of Ketcham et al (2012) relied on a third-party data source (formerly Wolters Kluwer Health, now Symphony Health Solutions) to generate these plan-specific prices. The cost calculator of Abaluck and Gruber (2011) held a given drug's price constant across all plans.…”
Section: B the Cost Calculatormentioning
confidence: 99%
See 1 more Smart Citation
“…This literature focuses heavily on whether enrollees make good choices, how limitations in consumer decision-making affect firm behavior, and how alternative choice architecture could improve consumer welfare. (See, for example, Abaluck andGruber 2011, 2013;Ericson 2014;Ketcham et al 2012;Kling et al 2012;Lucarelli, Prince, and Simon 2012;Zhou and Zhang 2012;and Heiss et al 2012.) Overall, the Medicare Part D literature suggests that even with robust entry, poor optimization by enrollees mitigates the salutary effects of competition.…”
Section: P R I O R R E S E a R C Hmentioning
confidence: 99%
“…Given that health insurance plans are complex financial objects, it is likely that many consumers are not fully informed about key plan design aspects or even their own medical expenditure risk (see, e.g., Kling et al 2012;Ketcham et al 2012;or Fang, Keane, and Silverman 2008). In addition, prior work such as Abaluck and Gruber (2011) and Barseghyan et al (2013) has shown that consumers may exhibit decision-making biases even conditional on their information sets.…”
mentioning
confidence: 99%